การศึกษาปฏิกิริยาระหว่างยาและเภสัชจลนศาสตร์ของยาเอเวอโรลิมุสเมื่อให้ร่วมกับยาลดไขมันอะทอวาสแตตินในผู้ป่วยที่ได้รับการปลูกถ่ายไต - อโนชา วนิชชานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Background: Everolimus (EVL), an inhibitor of mammalian target of rapamycin (mTOR), has been increasingly used in kidney transplant (KT) recipients as the main immunosuppressive drug. Dose-dependent hyperlipidemia induced by EVL commonly occurs up to 50 percent. Therefore, lipid-lowering drugs are common concomitant medication in KT recipients. Drug interaction between EVL and atorvastatin may occur since both drugs share common pharmacokinetics pathways. Interference of EVL drug levels may enhance risks of allograft rejection. Herein, we determine the effects of coadministration of EVL and atorvastatin. Methods: In this randomized, open-label, crossover study, twenty KT recipients were assigned (1:1) to receive EVL or EVL plus 20 mg atorvastatin for one-month period. One-month washout period was allowed during a crossover treatment. Plasma EVL concentrations were measured by homogeneous particle-enhanced turbidimetric immunoassay. Twelve-hour area under the time concentration curve (AUC0-12) of EVL was calculated using 10-point whole blood EVL concentrations (0, 0.5, 1, 1.5, 2, 2.5, 4, 6, 8, and 12 hours). Results: The mean AUC0-12 of EVL and EVL plus atorvastatin were 155.86 ± 41.67 and 151.33 ± 51.39 ng*hr/L, respectively (p=NS, pair t-test). During coadministration with atorvastatin, 10 patients had unchanged EVL AUC, whereas 6 patients had decreased EVL AUC more than 20 percents which may associated to clinical relevant and 4 patients had increased EVL AUC more than 20 percents. Most of patients AUC ware not affected by atorvastatin coadministration, while others have unpredicted change in AUC that may be from high intrapatient variability of everolimus. Conclusion: Coadministration of atorvastatin with EVL in KT recipients is safe and does not interfere with the EVL blood levels.